Enhanced electrical and thermal conductivity of modified poly(acrylonitrile-co-butadiene)-based nanofluid containing functional carbon black-graphene oxide. Issue 4 (2nd April 2016) - Kausar, Ayesha
ABSTRACT: Solution refluxing and high-pressure homogenization technique were reported for synthesizing nanofluids based on modified poly(acrylonitrile-co-butadiene) (M-PANB) as base fluid and carbon black (CB)/carbon black-graphene oxide (CB-GO) as filler. The physiochemical properties were studied to analyze the structure, morphology, thermal and electrical conductivity. FTIR analysis corroborated the structure of CB-GO nanobifiller and nanocomposite. Microstructure analysis of M-PANB/CB-GO revealed good dispersion of CB-GO nanosheets, while CB series showed granular distribution. XRD studies confirmed amorphous structure of M-PANB/CB-GO nanocomposite. Thermal conductivity of nanofluid was found to increase upto 1.41 W/mK for 10 wt.% CB-GO loading and electrical conductivity was increased to 2.5 × 10 −3 Scm −1 .